On the effect of the tension-compression ratio on forming of isotropic materials - Oliveira, Marta C. (2022)
It is generally believed that the choice of the yield criterion used to describe the plastic behaviour of isotropic metallic materials does not affect much the accuracy of the predictions of forming operations. For this reason, the von Mises yield criterion is widely used for modelling their plastic behaviour. However, according to the von Mises yield criterion, the ratio between the yield stresses in tension and compression is always 1.0. Nevertheless, materials can present same asymmetry, i.e. a strength differential (SD) effect. In this work, the yield criterion proposed by Cazacu et al. [1], is adopted to describe the mechanical behaviour of isotropic materials, with different levels of tension-compression asymmetry. Numerical simulations of the deep drawing of a cylindrical cup were performed considering these different virtual isotropic materials, in order to evaluate its impact on the thickness distribution and cup height. The analysis of the stress and strain paths, for material points initially located in the flange is performed, enabling the correlation between the thickness distributions predicted and the plastic strain ratios obtained analytically, using the yield function and the normality rule. The results show that even small changes in the tension-compression stress ratio can influence the strains distribution, in isotropic materials.